A TPACK-Based Analysis of Pre-service Primary Teachers' Understanding of Pancasila and Civic Education - Venna Puspita Sari; Dessy Norma Juita; Laely Farokhah (Pedagogik Journal of Islamic Elementary School, 2026)
The integration of pedagogy, content, and technology remains a key challenge in preparing pre-service primary teachers, particularly in Pancasila and Civic Education learning. This study aimed to explore the level of Technological Pedagogical Content Knowledge (TPACK) mastery among pre-service primary teachers enrolled in the Learning Pancasila and Civic Education in Primary Schools course. The research employed a qualitative case study design involving six pre-service primary teachers from a university in Jakarta, selected through purposive sampling based on variations in mid-term academic achievement. Data were collected through semi-structured interviews, classroom observations, and document analysis, including teaching modules, student assignments, and evaluation results. The collected data were analysed using thematic analysis to identify patterns related to students' conceptual understanding, pedagogical competence, initial technology integration, and supporting and constraining factors in the learning process. The findings show that students generally demonstrated adequate content understanding of Pancasila and Civic Education; however, their pedagogical understanding was not yet well developed, particularly in selecting and applying appropriate learning approaches and models. Technology integration tended to focus on technical and media-related aspects rather than supporting pedagogical strategies, indicating limited TPACK integration. Several constraints, such as limited theoretical literacy and learning context challenges, influenced students' ability to integrate pedagogy, content, and technology coherently. This study suggests that teacher education programs need to strengthen pedagogical scaffolding and reflective learning experiences to support more effective TPACK development among pre-service primary teachers.